أثر برنامج إرشادي لتنمية الصلابة النفسية لدى عينة من معلمات المرحلة الابتدائية بالقصيم - الفنيخ، لمياء سليمان (جامعة طنطا - كلية التربية, 2018)
هدفت الدراسة الحالية للتعرف على أثر برنامج إرشادي لتنمية الصلابة النفسية على عينة من معلمات المرحلة الابتدائية بمدينة عنيزة بمنطقة القصيم، وقد تكونت العينة من 10 معلمات تم تطبيق مقياس الصلابة النفسية عليهن إعداد كوبازا 1984 وتنقين مخيمر 2002، والبرنامج الإرشادي إعداد الباحثة، وقد استخدمت الباحثة المنهج التجريبي (تصميم المجموعة الواحدة)، وتوصلت النتائج إلى وجود فروق ذات دلالة إحصائية بين متوسطات رتب أفراد العينة في القياس القبلي والقياس البعدي للصلابة النفسية، ولم توجد فروق بين متوسطات رتب أفراد العينة في القياس البعدي والتتبعي.
The present study aimed to identify the effect of an indicative program on the development of psychological hardiness on a sample of primary school teachers in Onaizah, Qassim region the sample consisted of 10 teachers. The measure of psychological hardiness, which prepared by kobasa, S, C (1984 and revised by Mukhaimer (2002) and an indicative program prepared by the researcher have been used. The researcher used the researcher used the experimental approach (one group design). The results showed that there were statistically significant differences between the averages of the sample levels in the pre and post measurement scale of psychological hardiness, and there were no differences between the post and successive measurement in the experimental group.
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- الإضطرابات النفسية -- البرامج الإرشادية -- الصلابة النفسية -- التعليم الإبتدائي -- طلاب المرحلة الإبتدائية -- السعودية -- القصيم